Analysis of Hate Speech for the 2024 Election on Instagram Account @Bengkuluinfo - Gushevinalti, Gushevinalti; Riyandi, Alfian Putra (Semantik: Journal of Social, Media, Communication, and Journalism, 2024)
General elections (elections) are one of the political events that affect a country's social and political dynamics. In Indonesia, social media has a vital role in shaping perceptions and providing information to the public regarding issues related to elections. This study aims to investigate the influence of mass media elections on the issue of the 2024 Election in Bengkulu City. The research method used is qualitative, and interviews and observations of informants about using social media in the 2024 election on the @bengkuluinfo Instagram account were conducted. The results of this study show a variety of opinions on this social media, from strong support for specific candidates to skepticism about the integrity of the election process. This study explains views on political issues, including the use of social media, especially in the context of the 2024 election. In addition, the results of this study also provide input for related parties, including social media users and election institutions